Plea Bargaining and the Religious Cum Socio-Cultural concept of Yoruba Omoluabi in the Nigerian Political Landscape - Oke Olusegun Peter (Ilorin Journal of Religious Studies (IJOURELS), 2016)
The subtle incursion of plea bargaining into Nigeria’s criminal justice system during the trial of some influential personalities in the law courts in recent times has provoked a flurry of debates in the polity. The seemingly unending arguments on these debates about plea bargaining call for a scholarly attention, if the current efforts of government at eradicating corruption in the country will not be a mere political statement. On this issue, various researches have been carried out, some for the removal of this aspect of criminal justice system, others for its retention. This study is not out to consider either its removal or retention, but how it relates to the socio-cultural concept of Omoluabi among the Yoruba. It therefore, attempts to define what is meant by plea bargaining, introduction as to its history and its implication for the criminal justice system vis-a –vis the cultural concept of mol among the Yoruba. The methodology adopted in this work was the use of oral sources where adults were engaged to know their opinions about the Yoruba concept of Omoluabi as it relates to the subject matter. The deontological theory of Immanuel Kant constitutes the theoretical framework for this work. The theory emphasises on the rightness or wrongness of actions themselves as opposed to the consequences of such actions to the character and habit of the actor. The paper therefore finds among other things that the high rate of corruption came about due to the absence of the socio-cultural concept of mol among many political leaders in the country.